Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/agg2.20321
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus influences annual bluegrass competitiveness at seeding in perennial ryegrass and creeping bentgrass

Abstract: Annual bluegrass (AB; Poa annua L.) infestation is aided by phosphorus (P), but there is no information evaluating the effect of P on AB encroachment into turfgrass at seeded establishment. We hypothesized AB seedling survival and vigor will increase with P rates, compromising establishment of desired turfgrass species.Greenhouse pot studies evaluated the effect of P application rate on AB establishment or cover when seeded with perennial ryegrass (Lolium perenne L.) or creeping bentgrass (Agrostis stolonifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…In experiment 5, digital image analysis used to quantify turfgrass establishment from seed was highly correlated ( p < 0.001 and R ‐square = 0.92) to point intercept grid counts (Figure 4). Turfgrass coverage (%) from point intercept grid counts was typically higher than digital image analysis and more closely aligned to a visual estimate of coverage (data not shown; McNally et al., 2021). This may be due to the software in the digital image analysis detecting darker turfgrass leaves shadowed underneath other turfgrass leaves and quantifying them as “non‐green” when there is turfgrass in the pixel.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…In experiment 5, digital image analysis used to quantify turfgrass establishment from seed was highly correlated ( p < 0.001 and R ‐square = 0.92) to point intercept grid counts (Figure 4). Turfgrass coverage (%) from point intercept grid counts was typically higher than digital image analysis and more closely aligned to a visual estimate of coverage (data not shown; McNally et al., 2021). This may be due to the software in the digital image analysis detecting darker turfgrass leaves shadowed underneath other turfgrass leaves and quantifying them as “non‐green” when there is turfgrass in the pixel.…”
Section: Resultssupporting
confidence: 56%
“…Findings related to creeping bentgrass, and annual bluegrass establishment competition affected by phosphorus rates can be found in the work produced by McNally et al. (2021).…”
Section: Resultsmentioning
confidence: 94%
“…In the low pH soil, AB cover increased with P application rate from 3 kg ha −1 (18%) to 6 kg ha −1 (34%) to 9 kg ha −1 (42%), while 9 and 12 kg ha −1 of applied P had similar AB cover (42%–44%). Previous research found the greatest difference in AB response is typically between no P and the lowest P rate, with little differences thereafter (Kuo, 1993a; Lodge et al., 1990; McNally et al., 2022; Raley et al., 2013). However, previous research utilized much higher P rates (∼11 to 200 kg ha −1 P) and larger increments between rates than this study; previous research had suggested lower P rates may be required to reduce AB cover.…”
Section: Resultsmentioning
confidence: 94%
“…P is typically applied during seeded turfgrass establishment as it enhances seedling vigor, growth, and tillering (Frank & Guertal, 2013); however, it also promotes germination and establishment of AB from seed (Carrow et al., 2001; Nam‐Il et al., 2001). Previous research indicates low P rate applications to P‐deficient soils can reduce AB establishment from seed while providing sufficient vigor and health of CB establishing from seed (McNally et al., 2022). Increasing soil acidity will reduce AB germination (Ferguson, 1936), but there is little information on how soil acidity affects CB germination.…”
Section: Introductionmentioning
confidence: 99%
“…Related to these topics, extension educators have ample research manuscripts available as resources to build extension materials. For example, research on cultural practices in cool-season turfgrass systems has determined that minimal nitrogen and phosphorus rates, and more infrequent irrigation will minimize annual bluegrass populations (Cain et al, 2021;Kowalewski et al, 2022;McNally et al, 2022). In reference to annual bluegrass biology and physiology, findings produced by La Mantia and Huff (2011) were that annual bluegrass morphology and life cycle are plastic and strongly influenced by environment and cultural practices.…”
Section: Resultsmentioning
confidence: 99%